Extracting reaction mechanism analysis of Zn and Si from zinc oxide ore by NaOH roasting method - Chen, Bing; Shen, Xiao-yi; Gu, Hui-min; Shao, Hong-mei; Zhai, Yu-chun; Ma, Pei-hua (Journal of Central South University, 2017)
The orthogonal test was used to optimize the reaction conditions of roasting zinc oxide ore with NaOH aiming to comprehensively utilize zinc oxide ore. The optimized reaction conditions were molar ratio of NaOH to zinc oxide ore 6:1, roasting temperature 450 °C, holding time 150 min. The molar ratio of NaOH to zinc oxide ore was the most predominant factor affecting the extraction ratios of zinc oxide and silica. The mineral phase transformations were investigated by testing the phases of specimens obtained at different temperatures. The process was that silica reacted with molten NaOH to form Na 2 SiO 3 at first, then transformed into Na 4 SiO 4 with temperature rising. ZnCO 3 and its decomposing product ZnO reacted with NaOH to form Na 2 ZnO 2 . Na 2 ZnSiO 4 was also obtained. The reaction rate was investigated using unreacted shrinking core model. Two models used were chemical reaction at the particle surface and diffusion through the product layer. The results indicated that the reaction rate was combine-controlled by two models. The activation energy and frequency factor were obtained as 24.12 kJ/mol and 0.0682, respectively.